Thermal distribution and macrostructural characteristics of TIG-welded Cu/SS316L dissimilar joints: experimental and numerical study - Azwinur Azwinur; Agus Suprihanto; Mukhsinun Hadi Kusuma; Khoiri Rozi; Usman Usman; Surya Dharma; Hamdani Hamdani (Politeknik Negeri Lhokseumawe, 2026)
Dissimilar welding of copper (Cu) and Stainless Steel 316L (SS316L) presents significant challenges due to their large differences in thermal conductivity and melting temperature, which lead to asymmetric heat distribution and non-uniform penetration. This study aims to evaluate the effect of welding current on temperature distribution and macrostructural characteristics of TIG-welded Cu/SS316L joints using ERCuSi-A filler through an integrated experimental and numerical approach. Welding experiments were conducted at three current levels: 120 A, 135 A, and 150 A on 2.7 mm thick plates. Macrostructural examinations were performed to assess weld bead geometry and penetration behavior. Transient thermal simulations were carried out using ANSYS Workbench to predict temperature fields and thermal gradients. The results indicate that welding current significantly influences weld morphology and thermal behavior. At 120 A, the weld bead was relatively narrow with limited penetration on the Cu side due to rapid heat dissipation. At 135 A, a more uniform fusion profile was achieved, with simulated peak temperatures exceeding 1000°C and an improved penetration balance between Cu and SS316L. At 150 A, deeper penetration into SS316L was observed; however, the heating cycle became shorter and the temperature distribution more localized. Numerical results consistently showed asymmetric temperature fields, where heat diffused rapidly into Cu and concentrated in SS316L. The strong correlation between simulation and macrostructural observations confirms that thermal distribution governs weld geometry and penetration behavior. The 135 A current provides the most balanced fusion characteristics, making it suitable for Cu/SS316L dissimilar joints in heat-transfer applications.